Delayed Diagnosis of Hidradenitis Suppurativa and Its Effect on Patients and Healthcare System - Kokolakis, Georgios; Wolk, Kerstin; Schneider-Burrus, Sylke; Kalus, Stefanie; Barbus, Sebastian; Gomis-Kleindienst, Susana; Sabat, Robert (Dermatology (Basel), 2020)
Background: Hidradenitis suppurativa (HS) is a neglected chronic inflammatory disease with long delay in diagnosis. Besides pain, purulent discharge, and destruction of skin architecture, HS patients experience metabolic, musculoskeletal, and psychological disorders. Objectives: To determine the delay in HS diagnosis and its consequences for patients and the healthcare system. Methods: This was a prospective, multicenter, epidemiologic, non-interventional cross-sectional trial carried out in Germany and based on self-reported questionnaires and medical examinations performed by dermatologists. In total, data of 394 adult HS patients were evaluated. Results: The average duration from manifestation of first symptoms until HS diagnosis was 10.0 ± 9.6 (mean ± SD) years. During this time, HS patients consulted on average more than 3 different physicians – most frequently general practitioners, dermatologists, surgeons, gynecologists – and faced more than 3 misdiagnoses. Diagnosis delay was longer in younger and non-smoking patients. In most cases, HS was correctly diagnosed by dermatologists. The longer the delay of diagnosis, the greater the disease severity at diagnosis. Delayed HS diagnosis was also associated with an increased number of surgically treated sites, concomitant diseases, and days of work missed. Conclusion: This study demonstrates an enormous delay in the diagnosis of HS, which results in more severe disease. It also shows for the first time that a delay in diagnosis of a chronic inflammatory disease leads to a higher number of concomitant systemic disorders. In addition to the impaired health status, delayed diagnosis of HS was associated with impairment of the professional life of affected people.